Differences between Infected and Noninfected Patients with Acute Alcoholic Hepatitis - GY Minuk; A Cohen; V Thompson (Canadian Journal of Infectious Diseases)
The medical records of 97 patients with alcoholic hepatitis, including 20 with coexisting bacterial infections and 77 with no evidence of bacterial infection, were reviewed to determine whether commonly employed tests would be useful in distinguishing between the two groups. The results of the study revealed that patients with alcoholic hepatitis and bacterial infections had higher temperatures (38.4±0.9°C versus 37.9±0.7°C, P<0.05) and white blood cell counts (16.4±7.9 versus 11.2±6.4×109/L, P<0.005), but lower serum bilirubin levels (39±42 versus 115±152, P<0.05), than patients with alcoholic hepatitis alone. Patients with alcoholic hepatitis and bacterial infections also tended to reach maximum temperatures and white blood cell counts later in their hospital stay than patients with alcoholic hepatitis alone (5.1±5.3 versus 2.5±1.8 days, and 7.7±11.8 versus 4.4±5.7 days, respectively, P<0.05 and P<0.005). These results suggest that the extent and timing of peak abnormalities in body temperature, white blood cell count and serum bilirubin level may be of value in distinguishing patients with alcoholic hepatitis with bacterial infections from patients with alcoholic hepatitis alone.